The Emerald Shore - Mariconda, Barbara (Mariconda, Barbara. Voyage of Lucy P. Simmons, 2014)
"Lucy travels to Ireland in her magical house-turned-ship to find the pirate treasure that will end the magical curse haunting her family once and for all"--